Low‐frequency ESR studies on permeable and impermeable deuterated nitroxyl radicals in corn oil solution. (19th December 2017) - David Jebaraj, D.; Utsumi, Hideo; Milton Franklin Benial, A.
Abstract : Low‐frequency electron spin resonance studies were performed for 2 mM concentration of deuterated permeable and impermeable nitroxyl spin probes, 3‐methoxycarbonyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl and 3‐carboxy‐2, 2, 5, 5, ‐tetramethyl‐1‐pyrrolidinyloxy in pure water and various concentrations of corn oil solution. The electron spin resonance parameters such as the line width, hyperfine coupling constant, g factor, rotational correlation time, permeability, and partition parameter were estimated. The broadening of line width was observed for nitroxyl radicals in corn oil mixture. The rotational correlation time increases with increasing concentration of corn oil, which indicates the less mobile nature of spin probe in corn oil mixture. The membrane permeability and partition parameter values were estimated as a function of corn oil concentration, which reveals that the nitroxyl radicals permeate equally into the aqueous phase and oil phase at the corn oil concentration of 50%. The electron spin resonance spectra demonstrate the permeable and impermeable nature of nitroxyl spin probes. From these results, the corn oil concentration was optimized as 50% for phantom studies. In this work, the corn oil and pure water mixture phantom models with various viscosities correspond to plasma membrane, and whole blood membrane with different hematocrit levels was studied for monitoring the biological characteristics and their interactions with permeable nitroxyl spin probe. These results will be useful for the development of electron spin resonance and Overhauser‐enhanced magnetic resonance imaging modalities in biomedical applications. Abstract : L‐band ESR spectra of 2 mM deuterated permeable MC‐PROXYL in (a) pure water, (b) 10%, (c) 20%, (d) 30%, (e) 40%, and (f) 50% concentration of corn oil solution (the dotted line arrow indicates the aqueous peak, and solid line arrow indicates the corn oil peak).